Comparative Analysis of Learning With Jigsaw and Think Pair Share (TPS) on Mathematical Problem Solving Abilities on The Properties of Exponents in Grade X - Jois Febri Manik; Hardi Tambunan; Samuel Juliardi Sinaga (STABN RADEN WIJAYA WONOGIRI, 2021)
This study aims to analyze the comparison of cooperative learning models, Jigsaw and Think Pair Share (TPS), on students’ mathematical problem-solving abilities in the topic of exponent properties among tenth-grade students at SMK Free Methodist Medan in the 2025/2026 academic year. The research method employed was a quasi-experimental design with a pretest-posttest group design. The population consisted of all tenth-grade students at SMK Free Methodist Medan, while the sample included two classes: class X RPL taught using the Jigsaw model and class X TKJ taught using the TPS model. The research instrument was an essay test developed based on mathematical problem-solving indicators, and the data were analyzed using an independent samples t-test.The results of the study indicate that: (1) there is a significant difference in mathematical problem-solving abilities between students taught with the Jigsaw and TPS models (sig. 0.023 < 0.05), and (2) the Jigsaw learning model is more effective than the TPS model in improving students’ mathematical problem-solving abilities (sig. 0.011 < 0.05). Therefore, the Jigsaw learning model is recommended as a superior alternative cooperative learning strategy to enhance students’ mathematical problem-solving skills in the topic of exponents at the vocational high school level